Serum Concentrations of Losartan Metabolites Correlate With Improved Physical Function in a Pilot Study of Prefrail Older Adults. Issue 12 (4th May 2022) - Lee, Jessica L; Zhang, Cissy; Westbrook, Reyhan; Gabrawy, Mariann M; Nidadavolu, Lolita; Yang, Huanle; Marx, Ruth; Wu, Yuqiong; Anders, Nicole M; Ma, Lina; Bichara, Marcela-Dávalos; Kwak, Min-Ji; et al.
Abstract: Losartan is an oral antihypertensive agent that is rapidly metabolized to EXP3174 (angiotensin-subtype-1-receptor blocker) and EXP3179 (peroxisome proliferator-activated receptor gamma [PPARγ] agonist), which was shown in animal studies to reduce inflammation, enhance mitochondrial energetics, and improve muscle repair and physical performance. We conducted an exploratory pilot study evaluating losartan treatment in prefrail older adults (age 70–90 years, N = 25). Participants were randomized to control (placebo) or treatment (daily oral losartan beginning at 25 mg per day and increasing every 8 weeks) for a total of 6 months. Fatigue, hyperkalemia, and hypotension were the most observed side effects of losartan treatment. Participants in the losartan group had an estimated 89% lower odds of frailty (95% confidence interval [CI]: 18% to 99% lower odds, p = .03), with a 0.3-point lower frailty score than the placebo group (95% CI: 0.01–0.5 lower odds, p = .04). Frailty score was also negatively associated with serum losartan and EXP3179 concentrations. For every one standard deviation increase in EXP3179 (ie, 0.0011 ng/μL, based on sample values above detection limit) and EXP3174 (ie, 0.27 ng/μL, based on sample values above detection limit), there was a 0.0035 N (95% CI: 0.0019–0.0051, p < .001) and a 0.0027 N (95% CI: 0.00054–0.0043, p = .007) increase in average knee strength, respectively. Graphical Abstract: Losartan treatment was associated with lower concentrations of tumor necrosis factor α receptor 1; improvements in mitochondrial health biomarkers, such as higher serum concentrations of arginine and spermidine, with lower concentrations of nitrotyrosine, and lower extracellular concentrations of several intermediates of energy metabolism. Our findings suggest that losartan treatment improves molecular and clinical measures of frailty and may show a role for losartan's nonangiotensin PPARγ pathway.